A review of the dodo and its ecosystem: insights from a vertebrate concentration Lagerstätte in Mauritius - Rijsdijk, Kenneth F.; Hume, Julian P.; Louw, Perry G. B. De; Meijer, Hanneke J. M.; Janoo, Anwar; De Boer, Erik J.; Steel, Lorna; De Vos, John; Van Der Sluis, Laura G.; Hooghiemstra, Henry; Florens, F. B. Vincent; Baider, Cláudia; et al. (Journal of vertebrate paleontology, 2015)
The dodo Raphus cucullatus Linnaeus, 1758 , an extinct and flightless, giant pigeon endemic to Mauritius, has fascinated people since its discovery, yet has remained surprisingly poorly known. Until the mid-19th century, almost all that was known about the dodo was based on illustrations and written accounts by 17th century mariners, often of questionable accuracy. Furthermore, only a few fragmentary remains of dodos collected prior to the bird's extinction exist. Our understanding of the dodo's anatomy was substantially enhanced by the discovery in 1865 of subfossil bones in a marsh called the Mare aux Songes, situated in southeastern Mauritius. However, no contextual information was recorded during early excavation efforts, and the majority of excavated material comprised larger dodo bones, almost all of which were unassociated. Here we present a modern interdisciplinary analysis of the Mare aux Songes, a 4200-year-old multitaxic vertebrate concentration Lagerstätte. Our analysis of the deposits at this site provides the first detailed overview of the ecosystem inhabited by the dodo. The interplay of climatic and geological conditions led to the exceptional preservation of the animal and associated plant remains at the Mare aux Songes and provides a window into the past ecosystem of Mauritius. This interdisciplinary research approach provides an ecological framework for the dodo, complementing insights on its anatomy derived from the only associated dodo skeletons known, both of which were collected by Etienne Thirioux and are the primary subject of this memoir. Citation for this article: Rijsdijk, K. F., J. P. Hume, P. G. B. de Louw, H. J. M. Meijer, A. Janoo, E. J. de Boer, L. Steel, J. de Vos, L. G. van der Sluis, H. Hooghiemstra, F. B. V. Florens, C. Baider, T. J. J. Vernimmen, P. Baas, A. H. van Heteren, V. Rupear, G. Beebeejaun, A. Grihault, J. van der Plicht, M. Besselink, J. K. Lubeek, M. Jansen, S. J. Kluiving, H. Hollund, B. Shapiro, M. Collins, M. Buckley, R. M. Jayasena, N. Porch, R. Floore, F. Bunnik, A. Biedlingmaier, J. Leavitt, G. Monfette, A. Kimelblatt, A. Randall, P. Floore, and L. P. A. M. Claessens. 2015. A review of the dodo and its ecosystem: insights from a vertebrate concentration Lagerstätte in Mauritius; pp. 3-20 in L. P. A. M. Claessens, H. J. M. Meijer, J. P. Hume, and K. F. Rijsdijk (eds.), Anatomy of the Dodo (Raphus cucullatus L., 1758): An Osteological Study of the Thirioux Specimens. Society of Vertebrate Paleontology Memoir 15. Journal of Vertebrate Paleontology 35(6, Supplement).